Standard Method for Oral Health Education (OHE) Among Dental Professionals—A Mixed Analysis Approach - M Anita; S Bhuminathan; Sajid T. Hussain; R Pradeep Kumar; P Suganya; Charumathi Dhanushkodi (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aims to identify and evaluate the methods of oral health education (OHE) used by dental professionals in Chennai, India. Materials and Method: A cross-sectional survey was performed among 357 dentists to assess the standard technique for providing OHE. A 15-item questionnaire consisting of demographic variables and preferred method of OHE was distributed to the participants as Google Form. The collected data were tabulated and analyzed using descriptive analysis and analysis of variance (ANOVA). Results: Most participants (63.4%) reported the lecture method as the standard technique for delivering OHE. Among the study participants, 80% employed OHE aids, predominantly models (33.2%), pamphlets (16.8%), and AV projections (16.5%). Conclusion: The lecture method predominates among dental professionals for its perceived effectiveness and versatility. These findings underscore the importance of tailored educational strategies in oral health promotion, informed by demographic considerations and practitioner preferences, to enhance public health outcomes globally.